Comparison of alternative estimators of deep percolation in full and deficit irrigation - King, Jonathan, author; Sanford, William E., advisor; Butters, Gregory, committee member; Ronayne, Michael, committee member (Colorado State University. Libraries, 2015)
Farmers are increasingly selling their water rights to growing municipalities and abandoning their farms (buy and dry). A loss of food production in the midst of a growing population is a recipe for food shortages. There is a need for municipalities to meet their water demand from the water rights held by farmers while farmers continue to produce crops. One solution to prevent a 'buy and dry' scenario is for farmers to lease a portion of their water rights to municipalities and continuing to farm under a deficit irrigation program. For this solution to work Colorado Water Law requires that return flows be maintained for down gradient water users. According to Colorado Water Law, deep percolation is any water in the unsaturated zone below the root zone (Colorado Foundation for Water Education, 2009). Deep percolation is also assumed to result in groundwater recharge. The first objective of this study is to quantify deep percolation. The second objective is to determine an optimal deficit irrigation technique. The third objective is to evaluate the methods used to estimate deep percolation. This study investigated three different cornfields (referred to as Blocks) in 2011 in Greeley, Colorado. Each block practices different flood irrigation techniques for the purpose of finding an optimal deficit irrigation plan. Block 2 practices traditional flood irrigation, Block 1 applies water at the same frequency as in Block 2 but uses half the volume of water, and Block 3 only irrigates twice during the growing season but applies large volumes of water per irrigation. Three methods were used to estimate deep percolation in each block: Lysimeters, Unsaturated Zone Water Balance (UZWB), and Darcy Flux. At the same time as this study, the United States Department of Agriculture - Agricultural Research Service (USDA-ARS) estimated deep percolation using a water balance method. The lysimeter method found an average deep percolation for Block 1 at 58mm, Block 2 at 334 mm, and Block 3 at 238 mm. The UZWB method found an average deep percolation for Block 1 at 291mm, Block 2 at 518 mm, and Block 3 at 516 mm. The Darcy flux method found an average deep percolation for Block 1 at 209 mm, Block 2 at 160 mm, and Block 3 at 1,246 mm. The USDA-ARS found an average deep percolation for Block 1 at 391 mm, Block 2 at 838 mm, and Block 3 at 635 mm. Corn was harvested by the USDA-ARS at the end of the season and yields were estimated. Block 1 produced 149 bushels/acre, Block 2 produced 196 bushels/acre, and Block 3 produced 84 bushels/acre. All methods found the irrigation strategy applied to Block 3, in relation to the other Blocks, resulted in the greatest percentage of deep percolation compared to water applied. The lysimeter method determined that the irrigation plan used in Block 1 was the least efficient in creating deep percolation while the UZWB and Darcy Flux method found that the irrigation applied to Block 2 was the least efficient. Although Block 3 was the most effective in producing deep percolation it produced the least amount of corn. The UZWB method was thought to be the most valuable method in this study. Installation of the neutron probe access tubes caused minimal disturbance to the soils and this method investigated the entire unsaturated zone below the zero flux plane, which accounted for most vertical heterogeneity. The lysimeter method was the most direct method, but installation caused extensive soil disturbances. However, once the soil settled over time the lysimeter method provided consistent and reliable results. In this study the Darcy Flux Method provided the greatest range in results compared to the other methods. The primary concern in using the estimates from this method was the quality of the data collected by the sensors.